Hydrodeoxygenation of Isoeugenol over Ni- and Co-Supported Catalysts - Lindfors C; Maki-Arvela P; Paturi P; Aho A; Eranen K; Hemming J; Peurla M; Kubicka D; Simakova IL; Murzin DY (AMER CHEMICAL SOC, 2022)
Hydrodeoxygenation (HDO) of isoeugenol was investigated over several Ni (Ni/SiO2, Ni/graphite) and Co (Co/SBA-15, Co/SiO2, Co/TiO2, Co/Al2O3) catalysts at 200 and 300 degrees C under 30 bar hydrogen pressure in a batch reactor. The catalysts were prepared by an impregnation method and systematically characterized by X-ray diffraction, transmission electron microscopy, scanning electron microscopy and energy dispersive analysis, organic elemental, and thermogravimetrical analysis before and after the reaction. Analysis of the liquid, solid, and gaseous products was performed to identify isoeugenol transformation pathways. The maximum yield of the desired propylcyclohexane (PCH) (63%) and the highest sum of masses of reactants and products in the liquid phase based on GC results (GCLPA) (79%) were obtained over 10 wt % Co/SBA-15. HDO of isoeugenol over 11 wt % Co/SiO2 resulted in 50% PCH yield with a rather similar GCLPA of 73%. Low yields of PCH and the liquid phase mass balance closure were obtained over highly dispersed 15 wt % Co/Al2O3 and 15 wt % Co/TiO2. PCH yield was 60% over Ni/graphite and 44% over Ni/SiO2 after 4 h with GCLPA values of 73 and 70%, correspondingly. Overall PCH yields increased in the following order: Co/TiO2 < Co/Al2O3 < Ni/SiO2 < Co/SiO2 < Ni/graphite < Co/SBA-15. Regeneration and reuse of industrially relevant 11 wt % Co/SiO2 was succesfully demonstrated.